Five Alternative Myosin Converter Domains Influence Muscle Power, Stretch Activation, and Kinetics - Glasheen, Bernadette M. (Biophys J, 2018)
Muscles have evolved to power a wide variety of movements. A protein component critical to varying power generation is the myosin isoform present in the muscle. However, how functional variation in muscle arises from myosin structure is not well understood. We studied the influence of the converter, a myosin structural region at the junction of the lever arm and catalytic domain, using Drosophila because its single myosin heavy chain gene expresses five alternative converter versions (11a–e). We created five transgenic fly lines, each forced to express one of the converter versions in their indirect flight muscle (IFM) fibers. Electron microscopy showed that the converter exchanges did not alter muscle ultrastructure. The four lines expressing converter versions (11b–e) other than the native IFM 11a converter displayed decreased flight ability. IFM fibers expressing converters normally found in the adult stage muscles generated up to 2.8-fold more power and displayed up to 2.2-fold faster muscle kinetics than fibers with converters found in the embryonic and larval stage muscles. Small changes to stretch-activated force generation only played a minor role in altering power output of IFM. Muscle apparent rate constants, derived from sinusoidal analysis of the chimeric converter fibers, showed a strong positive correlation between optimal muscle oscillation frequency and myosin attachment kinetics to actin, and an inverse correlation with detachment related cross-bridge kinetics. This suggests the myosin converter alters at least two rate constants of the cross-bridge cycle with changes to attachment and power stroke related kinetics having the most influence on setting muscle oscillatory power kinetics.